PENGEMBANGAN OBJEK WISATA PANTAI BATU PINAGUT DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI BOROKO UTARA KECAMATAN KAIDIPANG KABUPATEN BOLAANG MONGONDOW UTARA - Bugis, Titi Sapitri; Kawung, Evelin J. R.; Lasut, Jouke J. (HOLISTIK, Journal Of Social and Culture, 2019)
Tourism development is one of the alternatives to addressing the local economy as well as efforts in supporting government policies. From social angles, tourism activities will expand the opportunity of labor both from the development activities of facilities and infrastructure and from various business sectors that are directly or indirectly related to tourism. Tourism activities in economic life can have a positive impact on creating jobs (business opportunities) that are wide enough.Batu Pinagut Beach is more visitors because of the growing tourism activities in the area of Batu Pinagut Beach tourism object that can provide good and broad activities or influences both positive impact and negative impact on Environmental conditions, economic, social and cultural conditions for the surrounding communities in the tourist areas, particularly North Boroko residents. Regardless of the form of tourism developments please keep in mind that the surrounding community is not for tourism, but instead must be on the foundation of the principle of "tourism for the community" principle of this kind of precedence the public interest than on Community needs.With the development of the Community tourism feeling the increase and income that began to change, among them the home form that was once made of wooden planks, now began to form permanently with wall walls, and home facilities More complete. The increased revenue is also a positive influence in education, parents who used to have no cost for their child's current education are able to higher education levels.Keywords: tourism, impact, community